Some Implications of Contrastive Lexicology for Bilingual Lexicography and Teaching Translation (With Special Reference to English-Arabic) - Radia BENZEHRA (Revue des Sciences Humaines)
The present article deals with the most important pedagogical question concerning translation. The question has to do with what to teach future translators. The importance of teaching the linguistic aspect of translation, mainly contrastive lexicology, before practice will be emphasized. In fact, the fundamental linguistic insight of our article lies in the importance we need to give to teaching lexical items, what they mean, how they are used in different linguistic and situational contexts in order to find their appropriate equivalents at the intralingual and especially the interlingual level. Observations concerning bilingual dictionaries, as the kind of contrastive information that can be added, are pointed out. Future bilingual dictionaries (English –Arabic and Arabic –English) should be able to capture the problematic features of translation in order to become a more valuable resource rather than just a checking device.